2022
DOI: 10.1111/bjop.12624
|View full text |Cite
|
Sign up to set email alerts
|

What ugly and beautiful photographs reveal about COVID‐19 lockdown experiences, everyday aesthetics and photography aesthetics

Abstract: Against the backdrop of the COVID-19 pandemic, which restricted our daily (visual) experiences, we asked people to take an ugly and beautiful photograph from within their homes. In total, 284 photographs (142 ugly and 142 beautiful) and accompanying statements were submitted and brought to light an intimate portrait of how participants were experiencing their (lockdown) home environment. Results revealed an aesthetic preference for (living) nature. Beauty and ugliness were also connected to good versus bad vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…As aesthetic appreciation is an intensely subjective experience, the choice of visual artworks was expected to impact it. A more efficient way to understand the interaction between imagery and art appreciation might have been to ask participants to select a number of artworks that they do like and then use them to examine possible imagery-aesthetic appreciation links, an approach similar to the method of production suggested by Fechner (1876) and used in different studies (Felisberti, 2021(Felisberti, , 2022Vissers & Wagemans, 2022). Finally, a larger follow-up study is needed to confirm (or disambiguate) some of the findings in this study, since there were four separated datasets, some of which did not contain all the variables for each of the participants (see methods).…”
Section: Discussionmentioning
confidence: 99%
“…As aesthetic appreciation is an intensely subjective experience, the choice of visual artworks was expected to impact it. A more efficient way to understand the interaction between imagery and art appreciation might have been to ask participants to select a number of artworks that they do like and then use them to examine possible imagery-aesthetic appreciation links, an approach similar to the method of production suggested by Fechner (1876) and used in different studies (Felisberti, 2021(Felisberti, , 2022Vissers & Wagemans, 2022). Finally, a larger follow-up study is needed to confirm (or disambiguate) some of the findings in this study, since there were four separated datasets, some of which did not contain all the variables for each of the participants (see methods).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the aforementioned exhibition study, we also found that beyond feeling moved and originality (predictive of both beauty and interest), meaningfulness and coherence of the photography series were predicting interest ratings (Vissers & Wagemans, 2021), indicating a role for more elaborate cognitive processes and meaning-making in aesthetic preferences of photographs. Furthermore, both the emotional aspects of photographs, and their meaning, came up as aesthetic strategies when people were asked to make their own ugly and beautiful photographs (during the COVID-19 lockdown; Vissers & Wagemans, 2023).…”
Section: Aesthetic Preferences For Artistic Photographsmentioning
confidence: 99%
“…Here, it would be interesting to let the viewer explain a bit more about their thoughts, and emotional processes. Previous studies already showed the value of giving participants more space to express their own aesthetic experiences (e.g., by letting people make their own photographs, and reflect on them; Felisberti, 2022; Vissers & Wagemans, 2023). These same studies have also highlighted the importance of making space to study both sides of the aesthetic coin (ugliness, as well as beauty).…”
Section: Aesthetic Preferences For Artistic Photographsmentioning
confidence: 99%
See 2 more Smart Citations